2020
DOI: 10.34297/ajbsr.2020.09.001456
|View full text |Cite
|
Sign up to set email alerts
|

Using Health Coaching to Improve Glycemic Control in African-American Diabetics: An Integrative Review

Abstract: Background: Diabetes continues to affect our population. As a complex disease, diabetes requires multifactorial risk-reduction strategies for appropriate glycemic control. While type II diabetes remains a global epidemic capable of being traced back to rapid increases in physical inactivity and obesity, type I diabetes is characterized by autoimmune destruction of beta cells in the pancreas. Diabetes is currently the 3rd leading cause of death in the US and the 7th leading cause of death worldwide. While the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…This is consistent with previous studies that have shown either mHealth or coaching can play a critical role in improving patient activation and self-management in Black patients with chronic disease. 21,22,53 In-person, health educator coaching reduced racial inequities in pain control for Black cancer patients, whereas an mHealth medication safety intervention improved blood pressure control in Black KT recipients (19)(20). Additionally, short-term studies in heart transplantation and KT demonstrated that mHealth led to improvements in medication adherence and hypertension management across racial groups (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous studies that have shown either mHealth or coaching can play a critical role in improving patient activation and self-management in Black patients with chronic disease. 21,22,53 In-person, health educator coaching reduced racial inequities in pain control for Black cancer patients, whereas an mHealth medication safety intervention improved blood pressure control in Black KT recipients (19)(20). Additionally, short-term studies in heart transplantation and KT demonstrated that mHealth led to improvements in medication adherence and hypertension management across racial groups (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Coaching and mobile health (mHealth) technologies for self-management and medication adherence have been shown to reduce hypertension, improve glycemic control, 19,20 and improve cancer pain management, especially in Black patients with these chronic diseases. 21,22 Notably, Black patients with chronic kidney disease, the same pool of patients who require KT, are more receptive to mHealth than their nonminority counterparts and think that mHealth can help them become engaged in their care.…”
mentioning
confidence: 99%
“…Selain itu, juga penelitian yang dilakukan Gresty (2017), terdapat hubungan yang signifikan pola makan dan hospital readmission. Paparan tersebut menegaskan bahwa pola diet yang kurang baik yang tidak sesuai dengan anjuran dapat menimbulkan terjadinya kenaikan kadar gula darah yang dapat menyebabkan timbulnya komplikasi pada pasien diabetes mellitus yang menyebabkan readmission akibat tidak patuhnya dalam melakukan diet yang baik (Andriani et al, 2021), sehingga intervensi Health coaching efektif dalam memperbaiki pola diet (Ruffin, 2017).…”
Section: Pembahasanunclassified
“…Precision education which teaches the association between behavior risk, lifestyle change, and AD can be psychologically beneficial, motivating, and programmatically concrete ( 26 ), especially among individuals with poor AD health risk appraisal ( 27 ). Furthermore, there is evidence for health coaching efficacy in low-income and underserved populations ( 28 , 29 ). Health coaching is especially beneficial for lifestyle change in people with numeracy and literacy deficits because it facilities participant interpretation of health risk information ( 30 ).…”
Section: Introductionmentioning
confidence: 99%